Accounting and Order. - Ezzamel, Mahmoud (Routledge studies in accounting., 2012)
This book draws on ancient Egyptian inscriptions in order to theorize the relationship between accounting and order. It focuses especially on the performative power of accounting in producing and sustaining order in society. It explores how accounting intervened in various domains of the ancient Egyptian world: the cosmos; life on earth (offerings to the gods; taxation; transportation; redistribution for palace dependants; mining activities; work organization; baking and brewing; private estates and the household; and private transactions in semi-barter exchange); and the cult of the dead.